Effects of Urbanization on Native Bird Species in Three Southwestern US Cities - Hensley, Christopher B.; Trisos, Christopher H.; Warren, Paige S.; MacFarland, Jennie; Blumenshine, Steve; Reece, Joshua; Katti, Madhusudan (Frontiers in Ecology and Evolution, 2019)
Urbanization presents novel challenges to native species by altering both the biotic and abiotic environments. The rapid pace of declines in species diversity and ecosystem services makes generalizations imperative. Studies have attempted to make generalizations about how species with similar traits respond to urbanization, although the results of such studies are geographically idiosyncratic. Here, we present a comparative study in three US cities: Fresno, California; Tucson, Arizona; and Phoenix, Arizona in an attempt to examine consistency in how urbanization affects native bird assemblages. Using presence-absence data to define regional and urban species pools, we tested for whether the urban avian assemblage is a random subset of the regional avian assemblages on the basis of both traits and phylogeny, and whether or not urbanization causes biotic homogenization among avian assemblages. We found little evidence for non-random trait shifts, with only distributions of diet guild, migratory status, and main habitat showing any significant change, and no evidence for non-random phylogenetic patterns in urban avian assemblages. We did however find some evidence for neutral processes in species’ occupancy of urban habitats. Species in the urban species pools have a higher median reporting frequency than species in the regional species pools in all three cities, although this difference is statistically significant in only one city. Cluster analyses show that levels of biotic homogenization are more severe in spring than in winter. The results presented here indicate that while urban avian assemblage structure may be determined by species’ traits, which may possess phylogenetic signal, simple occurrence in an urban area is likely due to random or neutral processes. The seasonality of homogenization has not to our knowledge been previously reported. We propose that the largely similar results from the three cities in this study result from structural similarities in the matrix habitats, and that the nature of matrix habitat and context of urbanization needs to be considered in future studies in order to resolve existing inconsistencies.